2007
DOI: 10.1001/archsurg.142.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Morbidity After Permanent Sacral Nerve Stimulation for Fecal Incontinence

Abstract: Permanent sacral nerve stimulation (SNS) is a promising emerging treatment for fecal incontinence. However, there is little data on morbidity and quality of life (QOL) during long-term stimulation.Design: Prospective trial to assess morbidity and QOL in patients treated with SNS. Median follow-up was 13 months (range, 1-42 months).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 34 publications
8
39
0
5
Order By: Relevance
“…The quality of life was also improved. 20 More recent studies have also confirmed the reduction of incontinence episodes 18,19,[21][22][23][24] 25 Apart from improving continence and quality of life, as demonstrated in our study, SNS is characterized by lowinvasive implantation and an uneventful course such as the one seen in our patients. SNS is also financially favorable in comparison to other surgical methods.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The quality of life was also improved. 20 More recent studies have also confirmed the reduction of incontinence episodes 18,19,[21][22][23][24] 25 Apart from improving continence and quality of life, as demonstrated in our study, SNS is characterized by lowinvasive implantation and an uneventful course such as the one seen in our patients. SNS is also financially favorable in comparison to other surgical methods.…”
Section: Discussionsupporting
confidence: 84%
“…17 This minimally invasive method can markedly improve continence in patients who have no morphological sphincter defect and would normally not benefit from the above-mentioned surgical reconstructions. [18][19][20][21][22][23][24][25][26] However, the exact mechanism of action for the effect of SNS on fecal incontinence has not yet been clarified. Fecal continence is a complex interaction of the puborectal muscle, anal sphincter, colon motility, and anorectal sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Most reports on sacral nerve stimulation comprise a small number of patients from single centers. 12,13 There has been no randomized trial.…”
Section: Resultsmentioning
confidence: 99%
“…Studies emerging from other centers use a score as the sole assessment tool for medium-to long-term follow-up in patients with SNM for fecal incontinence. 23,24 Using a score is of particular benefit for unscheduled visits and avoids the impracticalities of prolonged data collection from bowel diaries. Currently, no criterion standard exists as to which scoring system should be used, nor are there data showing how scoring systems and other tools should be combined to assess constipation.…”
Section: Discussionmentioning
confidence: 99%